The crystal structure of actarit, C10H11NO3 - Wang Fengfeng; Lu Xu; Mao Qiqi; Hu Xiaowen; Liu Yang (Zeitschrift für Kristallographie - New Crystal Structures)
C10H11NO3, orthorhombic, Pbca (no. 61), a = 13.3367(3) Å, b = 7.8091(2) Å, c = 18.7826(3) Å, V = 1956.16(7) Å3, Z = 4, Rgt(F) = 0.0393, wRref(F2) = 0.1131, T = 297 K.